General Practitioner Time Availability Per Inhabitant Per Year: A New Indicator to Measure Access to Primary Care - Beer, Laura; Cohidon, Christine; Senn, Nicolas (Frontiers in Health Services, 2022)
Introduction The number of general practitioners (GPs) per inhabitant, used commonly as an indicator of primary care (PC) access, reports only imprecisely on the true availability of GPs. The aim of this study is to develop a new PC access indicator that better reflects the availability of GPs to take care of patients at the population level, the average GP time availability per inhabitant per year. Methods We extracted the data from the Commonwealth Fund International Health Policy Survey of Primary Care Physicians conducted in 2015, including 11 Western countries and 12049 randomly drawn GPs. We built the indicator by combining two questions about weekly workload in hours and percentage of time spent on face-to-face contact with patients. The indicator was then adjusted regarding the number of GPs, the weeks worked per year and the country’s population size. Results On average, GPs worked 43 hours a week. The average time spent on face-to-face contact with patients was 30.5 hours/week (35 hours including emails and telephone contact), ranging from 22 hours in Sweden and 38 hours in France. The mean time available of GPs for face-to-face contact was 69 minutes/inhabitant/year, ranging from 38 minutes in Sweden to 118 minutes in Australia. Including email and telephone contact, the mean contact time rose to 79 minutes/ inhabitant/year, ranging from 48 minutes in Sweden to 127 minutes in Australia. Conclusion The new indicator provides an accurate and sensitive estimate of a GP’s true time availability at the population level. Results should be interpreted in the context of PC workforce organization, which may help guide GP workforce development.